Combination of a Chaperone Synthesis Inducer and an Inhibitor of GAPDH Aggregation for Rehabilitation after Traumatic Brain Injury: A Pilot Study - Elizaveta A. Dutysheva; Elena R. Mikhaylova; Maria A. Trestsova; Alexander I. Andreev; Danila Yu. Apushkin; Irina A. Utepova; Polina O. Serebrennikova; Eugenia A. Akhremenko; Nikolay D. Aksenov; Elizaveta I. Bon'; Sergey M. Zimatkin; Oleg N. Chupakhin; et al. (MDPI AG, 2022)
The recovery period after traumatic brain injury (TBI) is often complicated by secondary damage that may last for days or even months after trauma. Two proteins, Hsp70 and glyceraldehyde-3-phosphate dehydrogenase (GAPDH), were recently described as modulating post-traumatic processes, and in this study, we test them as targets for combination therapy using an inhibitor of GAPDH aggregation (derivative of hydrocortisone RX624) and an inducer of Hsp70 synthesis (the pyrrolylazine derivative PQ-29). The protective effect of the combination on C6 rat glioblastoma cells treated with the cerebrospinal fluid of traumatized animals resulted in an increase in the cell index and in a reduced level of apoptosis. Using a rat weight drop model of TBI, we found that the combined use of both drugs prevented memory impairment and motor deficits, as well as a reduction of neurons and accumulation of GAPDH aggregates in brain tissue. In conclusion, we developed and tested a new approach to the treatment of TBI based on influencing distinct molecular mechanisms in brain cells.